Psychological Factors Influencing Academic Achievement among Secondary School Students in Shamva district of Mashonaland Central Province in Zimbabwe. - Kasowe, Rittah (IJRDO- Journal of Educational Research, 2018)
The study investigated psychological factors influencing academic achievement of secondary school adolescents in Shamva district. The design for the study is ex-post-facto. The population for the study is 300 participants who were independently and randomly selected. Two standardized instrument tagged “Psychological Factors Assessment Questionnaire and Economics Achievement test was used to collect data for the study. The reliability of the instruments was 0.91and 0.86 respectively. Two hypotheses were formulated for the study. The data collected were analysed with an independent t-test. The data analysis showed that school phobia significantly influence academic achievement of students while achievement motivation does not. Based on the findings of this study, the researchers recommended among others that, teachers, parents, counsellors as well as the school authorities should be made to aware of the existing relationship between self-concept, anxiety, achievement motivation, and focus of control and academic achievement. This would enable them provide a better, useful and relevant educational, vocational, personal and social services that will enable secondary school learners , teachers and parents and the school authorities and the community  recognise and appreciate the presence of individual differences, among students and how best to reinforce them in every situation.